2019
DOI: 10.3390/pathogens8020067
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary View of Respiratory Syncytial Virus (RSV) Biology and Strain-Specific Differences

Abstract: Respiratory syncytial virus (RSV) is a human respiratory pathogen which remains a leading viral cause of hospitalizations and mortality among infants in their first year of life. Here, we review the biology of RSV, the primary laboratory isolates or strains which have been used to best characterize the virus since its discovery in 1956, and discuss the implications for genetic and functional variations between the established laboratory strains and the recently identified clinical isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 129 publications
(177 reference statements)
1
42
0
Order By: Relevance
“…Tracking the frequency, recurrence, and distribution of amino acid changes that may confer selective advantages is a key focus of INFORM-RSV. Recent strains and dominant genotypes have genetic differences from the prototype virus strain used in most vaccine research ( 43 ). Since antigenic site changes could alter viral antigenicity for vaccines and affect their susceptibility to MAbs, novel agents for prophylaxis cannot afford to miss their contemporary targets when they are eventually deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking the frequency, recurrence, and distribution of amino acid changes that may confer selective advantages is a key focus of INFORM-RSV. Recent strains and dominant genotypes have genetic differences from the prototype virus strain used in most vaccine research ( 43 ). Since antigenic site changes could alter viral antigenicity for vaccines and affect their susceptibility to MAbs, novel agents for prophylaxis cannot afford to miss their contemporary targets when they are eventually deployed.…”
Section: Discussionmentioning
confidence: 99%
“…Most HRSV pathogenesis studies have been performed with prototypic laboratory strains that are adapted to cell culture. Recent studies have suggested that these differ from contemporary clinical isolates in infectivity, replication kinetics and pathology [11]. Clinical isolates have been compared to laboratory-adapted HRSV-A2 showing that HRSV-A2 replicated to higher viral titres in HEp-2 cells and undifferentiated primary paediatric epithelial cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Each CDC panel consisted of 20 freeze‐dried samples prepared from RSV‐infected or uninfected cell cultures (Table 1). Four RSV strains were used 15353_ON1 (RSV A) 15,16 RSV Long strain (RSV A), 17 53530_BA (RSV B), 18 and 209_GB3 (RSV B) 19,20 . Viruses were grown using Hep‐2 monolayer with 10% MEM + 20 mM HEPES and inactivated by gamma‐irradiation.…”
Section: Methodsmentioning
confidence: 99%